PEMODELAN BANGKITAN PERGERAKAN PADA TATA GUNA LAHAN SEKOLAH DASAR SWASTA DI SURABAYA - Harry Patmadjaja; Rudy Setiawan (Institute of Research and Community Outreach - Petra Christian University, 2002)
Elementary School is a common location for traffic congestion especially every morning. This condition can be avoided if the elementary school planner can predict the trip generation of that school. The aim of this research is to make a mathematical model of trip generation for elementary school land use at Surabaya. Research has been done to eight private elementary school using Pearson Correlation Analysis, Simple Regression Analysis, and Stepwise Regression Analysis to obtain the most significant trip generation model. Arrival rate and service rate distribution was analyzed using Chi-Square Distribution Fitting method to obtain arrival rate and service rate characteristic. From the analysis, the most significant trip attraction model is Y = -867,9 + 194.Log X1 + 274.Log X8 + 177.Log X5, in which Y is number of student vehicle, X1 is number of elementary student, X8 is total area of classroom, and X5 is classroom capacity. The most significant trip production model is Y= -797,2 + 311.Log X1 + 164.Log X8 +79.Log X15, in which Y is number of student vehicle, X1 is number of elementary student, X8 is total area of classroom, and X15 is ratio between number of teacher and classroom. Several elementary school characteristics that influence traffic congestion are: number of student, number of queue lane, number of entrance, and vehicle occupancy. Abstract in Bahasa Indonesia : Sekolah dasar merupakan salah satu lokasi yang sering mengalami masalah kemacetan lalulintas. Hal tersebut bisa dicegah bila pemilihan lokasi sekolah dilakukan dengan mempertimbangkan perkiraan bangkitan pergerakan yang akan terjadi. Tujuan dari penelitian ini adalah untuk membuat model bangkitan pergerakan (trip generation) kendaraan roda empat (pribadi dan antar jemput) akibat pembangunan sekolah dasar swasta di Surabaya. Survey dilakukan pada delapan sekolah dasar swasta di Surabaya. Hasil survey dianalisis dengan metode Pearson Correlation, Simple Linear Regression, dan Stepwise Regression untuk mendapatkan model persamaan matematis yang paling signifikan. Distribusi laju kedatangan dan laju pelayanan dianalisa dengan metode chi square distribution fitting untuk mengetahui karakteristik laju kedatangan dan laju pelayanan kendaraan pengantar siswa. Hasil analisa menunjukkan model terbaik untuk meramalkan pergerakan yang tertarik menuju ke sekolah dasar swasta (trip attraction) adalah Y = -867,9 + 194.Log X1 + 274.Log X8 + 177.Log X5, dimana Y adalah jumlah kendaraan pengantar, X1 adalah jumlah siswa sekolah dasar, X8 adalah luas total kelas, dan X5 adalah kapasitas kelas. Sedangkan model terbaik untuk meramalkan pergerakan yang berasal dari sekolah dasar swasta (trip production) adalah Y= -797,2 + 311.Log X1 + 164.Log X8 +79.Log X15, dimana Y adalah jumlah kendaraan penjemput, X1 adalah jumlah siswa sekolah dasar, X8 adalah luas total kelas, dan X15 adalah jumlah guru dibagi jumlah kelas. Beberapa karakteristik sekolah dasar yang mempengaruhi kelancaran lalulintas adalah: jumlah siswa, jumlah lajur antrian, jumlah pintu masuk, dan okupansi kendaraan.